EKSTRAKSI ASAP CAIR DARI PELEPAH KELAPA SAWIT MENGGUNAKAN PELARUT ETIL ASETAT DAN HEKSANA - Seri Maulina, Fakhradila, Nurtahara (Universitas Sumatera Utara, 2018)
The compounds in the liquid smoke can be extracted using a polar and non polar solvent. Polar and non polar solvents are often used for the extraction of phenol compounds from plants. Extraction of compounds in liquid smoke was performed by using ethyl acetate (polar) and hexane (non polar) solvents at 40°C, 55°C and 70°C with 60 minutes, 120 minutes, 180 minutes. The highest yield of ethyl acetate solvent was obtained at 70oC and the extraction time for 3 hours was 66% and the lowest was at 40oC and the extraction time for 1 hour was 30%. While on hexane solvent the highest rendement value was obtained at 70oC and the extraction time for 3 hours was 58% and the lowest was at 40oC and the extraction time for 1 hour was 12 %.